TI-ZEL: A MIND MAP MODEL OF ENGLISH SKILLS HABITUATION FOR NON-ENGLISH DEPARTMENT - Nur Rahmiani (English Language and Literature International Conference (ELLiC) Proceedings, 2021)
The article aims at introducing a new systematic and structured innovation of overcoming the problems of mastering the English language that may be found almost in many formal educational institutions, especially in the non-English department at Islamic higher education institutions in Indonesia. Employing the stages of analysis and assessment of the quality of issues and causal factors, the paper introduces a foreign language habituation model design that can be applied in tertiary institutions, especially for speaking skills improvement. Applying a design and developmental research method, the paper exposes the Analysis-Design-Develop-Evaluation workflow that is centered on product development, product contribution to theory, and proof of practice being practiced at Shariah Faculty of IAIN Pontianak. The work shows a Mind Map Habituation Model of Academic and Studentship Services based on Time Zone in English Language (Ti-ZEL), which has been adjusted to the needs of the Faculty needs in order to improve foreign language skills in a comprehensive scope ranging from students, academic staff, lecturers, and leaders. In the future, this model can be developed with an online-based design that meets the needs of long-distance habituation due to the COVID-19 pandemic conditions.